Color stability after accelerated aging of two silicones, pigmented or not, for use in facial prostheses - Daniela Nardi Mancuso; Marcelo Coelho Goiato; Daniela Micheline dos Santos (Sociedade Brasileira de Pesquisa Odontológica, 2009)
One of the greatest challenges faced by buccomaxillofacial prosthetists is to reproduce the patient's exact skin color and provide adequate esthetics. To reach this objective, professionals must use materials with easy characterization and that maintain color over long periods of time. The objective of this study was, thus, to evaluate the color stability of two types of silicones, Silastic 732 and Silastic MDX4-4210. Twenty-four test specimens were made from each type of silicone and were divided into a colorless group and groups intrinsically pigmented with ceramics, cosmetics or iron oxide. The specimens were submitted to an accelerated system of aging for non-metallic materials. Readings were carried out initially and after periods corresponding to 163, 351, 692 and 1,000 hours of aging, using a reflection spectrophotometer analysis, and color alterations were calculated by the CIE L*a*b* system. The data were submitted to variance analysis and Tukey's test at a 5% level of probability. The results demonstrated that, irrespective of the period of time analyzed, all the materials underwent some type of chromatic alteration (ΔE > 0). The test specimens made with Silastic 732 and MDX4-4210, without pigmentation, presented the lowest color alteration values after 1,000 hours of aging. Of the pigments, ceramic presented the lowest color alteration values and cosmetic powder presented the highest values. Thus, it may be concluded that the materials without the incorporation of pigments presented similar color alteration values, and did not differ statistically. The cosmetic powder used in this study was the pigment that most altered the color of the test specimens.